A Comparative Study of LAMP and PCR in Relation to Time and Cost - Rawnuck, Tanzila; Reza, Md Selim; Rahman Khan, Mohammad Jahidur; Khanam, Rashida Akter; Munshi, Saif Ullah (Journal of Shaheed Suhrawardy Medical College, 2022)
Background: The Loop-mediated isothermal amplification (LAMP) represents a very sensitive, easy to use, and less time consuming diagnostic method. Aims: The aim was to establish a simple, cost-effective, molecular technique. Materials and methods: An analytical study was conducted using two hundred acute serum samples using two different molecular techniques; qPCR and LAMP to standardize a costeffective and less time-consuming technique. Results: The cost of in-house LAMP reagents was one-ninth of the cost of commercial qPCR. Consume cost was 23 times less than qPCR besides, lab setup cost was 92 times less than qPCR. More importantly, LAMP requires 5-6 times less time duration than qPCR. Conclusion: Due to its simple short-time operation with low cost, it would be a prevalent molecular technique globally, particularly in Bangladesh. J Shaheed Suhrawardy Med Coll 2020; 12(2): 72-75